FROM SEGREGATION TO CELEBRATING DIVERSITY - Bruveris, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The move from segregation of students with behaviour difficulties to one of inclusion required teachers to make a significant paradigm shift. This paper reviews the strategies used by the New South Wales state education department to facilitate, over time, paradigm shifts in teacher thinking. Are there factors which limit the success of these strategies? What can be learnt from this?